2020
DOI: 10.1155/2020/8168479
|View full text |Cite
|
Sign up to set email alerts
|

Frequentist and Bayesian Regression Approaches for Determining Risk Factors of Child Mortality in Ghana

Abstract: Background. Child mortality is a global health problem. The United Nations’ 2018 report on levels and trends on child mortality indicated that under-five mortality is one of the major public health problems in Ghana with a rate of 60 deaths per 1000 live births. To further mitigate this problem, it is important to identify the drivers of under-five mortality in order to achieve the United Nations SDG Goal 3 target 2. Methods. In this study, we investigated the effects of some selected risk factors on child mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…This study also revealed that children from mothers having secondary school and above educational background had a fewer risk of death than those from uneducated ones. This is in agreement with previous studies conducted in Gilgel-Gibe Field Research Center of Southwest Ethiopia, 27 the whole Ethiopia, 16 , 23 , 28 Ghana, 21 , 24 , 29 and countries of Sub-Saharan Africa. 30 …”
Section: Discussionsupporting
confidence: 93%
“…This study also revealed that children from mothers having secondary school and above educational background had a fewer risk of death than those from uneducated ones. This is in agreement with previous studies conducted in Gilgel-Gibe Field Research Center of Southwest Ethiopia, 27 the whole Ethiopia, 16 , 23 , 28 Ghana, 21 , 24 , 29 and countries of Sub-Saharan Africa. 30 …”
Section: Discussionsupporting
confidence: 93%
“…A child born to adolescent mothers exhibits fragile health outcomes and leads to a higher risk of under-five death [43]. Different studies [19,32,33] have shown that younger age (generally below 20 years) of mother at childbirth revealed significantly higher odds of under-five mortality with reference to middle age (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) of childbearing; however, there is no particular common age to segregate. Another prime dominant factor of childhood mortality is the place of residence.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Figure 2, 22 eligible studies (listed in Table 1) were selected for systematic review from four different regions, namely, Africa, South-East Asia, Eastern Mediterranean, and Western Pacific. Out of 22 studies, 18 studies were conducted in 11 countries in the Africa region (Burkina Faso [19][20][21]: 3, Ethiopia [22][23][24]: 3, Nigeria [25][26][27]: 3, Ghana [28,29]: 2, Lesotho [30]: 1, sub-Saharan (combine study of five-country; Chad, Democratic Republic (DR) of Congo, Mali, Niger, and Zimbabwe) [31]: 1, Zambia [32]: 1, Kenya [33]: 1, DR Congo [34]: 1, Sierra Leone [35]: 1, and Tanzania [36]: 1). One study included was conducted in Nepal [37] and another one in Bangladesh [38] from South-East Asian region.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…The Bayesian methods have also been proved to be better than classical methods in analyzing the utilization of ANC in Ethiopia [ 28 ]. The said Bayesian methods have also provided efficient results for analyzing the important determinants of maternal health care in Ghana [ 29 ], India [ 30 ], Nigeria [ 31 ], and Ethiopia [ 25 , 32 ]. However, to the best of our knowledge, the Bayes methods have not yet been used to analyze the utilization of MHS in the country.…”
Section: Introductionmentioning
confidence: 99%